2020
DOI: 10.1016/j.heliyon.2020.e04762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ti–35Nb–7Zr–5Ta and Ti–6Al–4V hydrofluoric acid/magnesium-doped surfaces obtained by anodizing

Abstract: Objectives Development of a new generation of stable β alloy, free of aluminum or vanadium and with better biological and mechanical compatibility and evaluate the surface properties of Ti–6Al–4V and Ti–35Nb–7Zr–5Ta after anodization in hydrofluoric acid, followed by deposition of different electrolyte concentrations of magnesium particles by micro arc-oxidation treatment. Methods Disks were anodized in hydrofluoric acid. After this first anodization, the specimens rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Ti-35Nb-7Zr-5Ta alloy was obtained by the arc-voltaic casting method, with inert atmosphere, controlled by vacuum pump and argon flow. After casting, the ingots were subjected to a heat treatment of homogenization at 1000 °C for 8 h (vacuum), then were forged and machined in the form of discs [ 4 ]. All discs were submitted to finishing and polishing in a polish machine with silicon carbide-SiC sandpaper (Norton Abrasivos do Brasil, São Paulo, SP, Brazil) of 120, 320, 600, 1200 and 2000 grains.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ti-35Nb-7Zr-5Ta alloy was obtained by the arc-voltaic casting method, with inert atmosphere, controlled by vacuum pump and argon flow. After casting, the ingots were subjected to a heat treatment of homogenization at 1000 °C for 8 h (vacuum), then were forged and machined in the form of discs [ 4 ]. All discs were submitted to finishing and polishing in a polish machine with silicon carbide-SiC sandpaper (Norton Abrasivos do Brasil, São Paulo, SP, Brazil) of 120, 320, 600, 1200 and 2000 grains.…”
Section: Methodsmentioning
confidence: 99%
“…For the CaP group, we used a protocol for the formation of micropores with incorporation of Ca 2+ and PO 4 3− , in an electrolyte composed of 0.04 mol/L of sodium β-glycerophosphate (Sigma-Aldrich Co, St Loius, Mo, USA) plus 0 .35 mol/L calcium acetate (Sigma-Aldrich Co, St Loius, Mo, USA). The current source was adjusted to 300 V with varying electrical current intensity, starting at 2.5 A, for 60 s. For the Mg group, we used a magnesium acetate electrolyte at a concentration of 0.1 mol/L [ 4 ] with a voltage of 200 V, current of 2 A for 60 s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that Mg 2+ enhances the initial biological response surrounding implants and augments the biomechanical strength of bone integration ( Reis et al, 2020 ). Furthermore, as a biodegradable element, magnesium has attracted extensive research attention for its incorporation into biomaterials to facilitate stem cell differentiation into osteoblasts and amplify bone formation ( Sun et al, 2013 ; Li X. et al, 2018 ; Nabiyouni et al, 2018 ; Zhao Z. et al, 2021 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%